2016
DOI: 10.1515/ijeeps-2016-0056
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of Grid Connected PV-Biomass Integrated Energy System in Egypt

Abstract: The aim of this paper is to present a feasibility study of a grid connected photovoltaic (PV) and biomass Integrated renewable energy (IRE) system providing electricity to rural areas in the Beni Suef governorate, Egypt. The system load of the village is analyzed through the environmental and economic aspects. The model has been designed to provide an optimal system configuration based on daily data for energy availability and demands. A case study area, Monshaet Taher village (29° 1′ 17.0718”N, 30° 52′ 17.04”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…In other to achieve this, HOMER combines capital cost, fuel cost, Operation and Maintenance (O and M) cost and replacement cost at the buildup of the project. The important trade-off is the capital versus operating cost that shows that renewables have high capital cost but low operating cost while diesel have low capital cost but high operating cost (Barakat et al 2016;Givler and Lilienthal 2005).…”
Section: Homer Simulationmentioning
confidence: 99%
See 3 more Smart Citations
“…In other to achieve this, HOMER combines capital cost, fuel cost, Operation and Maintenance (O and M) cost and replacement cost at the buildup of the project. The important trade-off is the capital versus operating cost that shows that renewables have high capital cost but low operating cost while diesel have low capital cost but high operating cost (Barakat et al 2016;Givler and Lilienthal 2005).…”
Section: Homer Simulationmentioning
confidence: 99%
“…The amount of agricultural residue generated annually in tons, G A can be obtained from (Barakat et al 2016)…”
Section: Biomass Fuel Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Reference [13] carried out resource assessments using similar approaches in Nigeria, a case study in SSA. Literature [14] carried out an assessment of grid-connected PV and Biomass energy system to provide electricity for rural communities in Egypt. The results obtained revealed that the hybrid renewable energy system proves efficient for emissions and cost reductions.…”
Section: Introductionmentioning
confidence: 99%